Prostate atypia: Does repeat biopsy detect clinically significant prostate cancer?. Issue 7 (16th January 2015) - Dorin, Ryan P.; Wiener, Scott; Harris, Cory D.; Wagner, Joseph R.
<x xml:space="preserve">Abstract</x> Background While the treatment pathway in response to benign or malignant prostate biopsies is well established, there is uncertainty regarding the risk of subsequently diagnosing prostate cancer when an initial diagnosis of prostate atypia is made. As such, we investigated the likelihood of a repeat biopsy diagnosing prostate cancer (PCa) in patients in which an initial biopsy diagnosed prostate atypia. METHODS We reviewed our prospectively maintained prostate biopsy database to identify patients who underwent a repeat prostate biopsy within one year of atypia (atypical small acinar proliferation; ASAP) diagnosis between November 1987 and March 2011. Patients with a history of PCa were excluded. Chart review identified patients who underwent radical prostatectomy (RP), radiotherapy (RT), or active surveillance (AS). For some analyses, patients were divided into two subgroups based on their date of service. RESULTS Ten thousand seven hundred and twenty patients underwent 13, 595 biopsies during November 1987‐March 2011. Five hundred and sixty seven patients (5.3%) had ASAP on initial biopsy, and 287 (50.1%) of these patients underwent a repeat biopsy within one year. Of these, 122 (42.5%) were negative, 44 (15.3%) had atypia, 19 (6.6%) had prostatic intraepithelial neoplasia, and 102 (35.6%) contained PCa. Using modified Epstein's criteria, 27/53 (51%) patients with PCa on repeat biopsy were determined to have clinically significant tumors. 37 (36.3%) proceeded to RP, 25 (24.5%) underwent RT, and 40 (39.2%) received no immediate treatment. In patients who underwent surgery, Gleason grade on final pathology was upgraded in 11 (35.5%), and downgraded 1 (3.2%) patient. CONCLUSIONS ASAP on initial biopsy was associated with a significant risk of PCa on repeat biopsy in patients who subsequently underwent definitive local therapy. Patients with ASAP should be counseled on the probability of harboring both clinically significant and insignificant prostate cancer. Prostate 75:673–678, 2015. © 2015 Wiley Periodicals, Inc.